A Multiple Case Study that Looks at the Implementation of character Education in English Classroom - Usep Syaripudin; Siti Aisyah (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2016)
This research observed and analyzed the implementation of character education in English classrooms. It sought to find out how English teachers develop and select materials and strategies for implementing character education in their classroom, how the English teachers implement and integrate character education in their classroom, and what factors the teachers found to be the inhibiting and supporting system for implementing character education in their school. Three teachers from three schools – a public vocational school, a public senior high school, and a religious-based public high school – participated in this research as the respondents. The purpose of involving three different type of schools was that this research needed to observe the implementation of character education in three different settings. By implementing multiple case study, this research gathered data through interview and observation. This research found that teachers in the two schools – vocational and senior high school – begun the implementation of character education by developing a plan consisted of what character they need to develop and what materials that triggered students’ interest. Moreover, this research also found that the two schools share similar strategies in implementing character education as follows: using authentic materials, verbal instructions, and cultural approach. Meanwhile, in the religious-based senior high school, the teacher did not specifically develop and select materials intended to implement character education since the school had already subjects and extracurricular programs in religion teaching and intended to develop students’ character. Lastly, this research found that the three schools share similar supporting and inhibiting factors in implementing character education namely lack of good examples in school, family, and community, lack of partnership between school, parents, and community member, and lack of commitment among the school community members to support the character education in school. And the supporting system they had were that the schools had already developed code of conducts, rules, and extracurricular programs intended to develop students’ character.